Sirenomelia, the mermaid baby: a case report - Joshi, Reetika; Duomai, Veino Kuveio; Sangma, Bianchi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Sirenomelia sequence or mermaid syndrome is a rare congenital structural anomaly characterized by different degrees of fusion of lower limbs, thoracolumbar spinal anomalies, sacrococcygeal agenesis, genitourinary and anorectal atresia. The incidence of sirenomelia is 0.8-1 cases/ 105 births with male to female ratio being 3:1. A malformations patient with 40 weeks of gestation admitted with complaints of decreased fetal movements for one week. An emergency C-section was done in view of term pregnancy with severe oligohydramnios and intrauterine growth restriction with poor bishop’s score. A 1.9 kg live baby with fused lower limbs was delivered. The new born baby had narrow chest, fused both lower limbs and feet with 11 toes, small rudimentary external genitalia, imperforate anus and single umbilical artery. The baby also had features of potter’s facies including low set large ears, receding chin and prominent infraorbital folds. Sirenomelia is a rare fatal congenital anomaly. Early detection by prenatal ultrasound will help in timely termination of pregnancy.